(untitled) (Research, Society and Development, 2022)
The vast majority of cases of anxiety and depression end up harming people’s routine, as many of them leave their routine activities because they are in a moment of crisis. Objective: To analyze the prescriptions of special control drugs in a commercial pharmacy in the municipality of Ramilândia in Paraná. Methodology: Descriptive statistical research with a quantitative approach, carried out through the analysis of documentary data collection of prescriptions and prescriptions notifications of psychotropic drugs dispensed from January 2019 to December 2021. Results: During the research period, they were analyzed 1331 C1 recipes and B1 recipes notifications in total. The anxiolytic with the highest number of prescriptions was Clonazepam, and among the antidepressants, Quetiapine was the most indicated. There was a prevalence of dispensing psychoactive drugs for females and for the adult age group (age between 25 and 59 years). Regarding medical specialties, general practitioners were the physicians who most prescribed psychotropic drugs. Conclusions: According to the evolution in the analyzed period, it was observed that in this pharmacy there was no increase in the demand for dispensing psychotropic drugs during the COVID-19 pandemic period.